Europe’s economic geology potential enables reducing its geopolitical dependence on critical and strategic minerals - Arvanitidis, Nikolaos (Technical Annals, 2024)
Mineral raw materials were for many years the missing link in the climate debate. It is now evident that climate goals can’t be met without them. Mineral-based lithium battery and neodymium magnets value chains are not in balance between upstream-downstream efforts e.g. electric vehicles boom when energy transition mineral resources are yet not secured, Considering the long period of time (from exploration to mining takes about 15 years) needed for the mineral value chains to be fully operational, the technologies addressing the implementation plan of climate change goals might not always readily available due to lack of the mineral resources needed. However, Europe’s opportunity to become self-sufficient in mineral raw materials supply from own sources and resources, is strongly favored by its geological setting and metallogenetic evolution. Critical and strategic mineral raw materials from European primary and secondary resources produced in Europe can be taken as a guarantee for high standards in social, environmental, and economic terms. Elements and practices related to circular economy, responsible sourcing and resource efficiency addressed by the new EU industrial strategy, should be particularly considered. Major European mineral belts, such as Fennoscandian, Iberian, Carpathian-Balkan, host highly potential exploration targets challenging the likelihood for discovery of new resources and feasible mining prospects. At this stage recycling is not significant resource provider for some of the critical and strategic mineral raw materials. For the EU and the rest of the world to develop mineral supply chains, less dependent on China, strengthening key technology value chains, including processing, refining and metallurgy facilities, seems to be a dominant target.